TIPE PERILAKU BIROKRASI DALAM PROSES PERUMUSAN KEBIJAKAN PUBLIK (STUDI PADA PROSES PERUMUSAN RENCANA KERJA PEMERINTAH DAERAH KABUPATEN SIDENRENG RAPPANG) - Jamaluddin Ahmad (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2010)
The consistency of regional government budget (APBD) is actually reflectied from adjustment planning and budgetting program, which is really determined by formulating process of regional government planning (RKPD) every year. Formulating process is bureaucracy responsibility, so most of behaviors of bureaucracy are dominated. This research aimed at: (1) describing behaviors of bureaucracy types in formulating process regional government planning Sidenreng Rappang Regency, and (2) explain the formulating process of regional government planning principles with behaviors of bureaucracy types in Sidenreng Rappang Regency. This research was a descriptive-qualitative research, that is describing behaviors of bureaucracy types in formulating process regional government planning. In the collection of data, the writer acted as the research instrument. The collected data included behaviors of bureaucracy types, external environment models interaction with behaviors of bureaucracy types, and good governance principles implementation. There were two sources of data, document and informants. The data were collected through documentation, interviews, and observation. The data were analyzed further by using descriptive-qualitative analysis. The results of the research showed that between behaviors of bureaucracy types consists of: career staf type, politics type, professional type, and missioner type, which dominated by the career staf type in formulating process regional government planning Sidenreng Rappang Regency. Whereas, the formulating process regional government planning principles with behaviors of bureaucracy types determined by phase adjustment of planning process with learning to old public administration, new public management, new public service, and decision making anatomies.